EPIDEMIOLOGI KASUS BEDAH PLASTIK DI RSUD SYARIFAH AMBAMI RATO EBHU BANGKALAN, PENELITIAN RETROSPEKTIF DUA TAHUN - Primadina, Nova (Jurnal Ilmu Kesehatan dan Kesehatan, 2017)
Abstract: Syarifah Ambami Rato Ebhu Bangkalan Hospital is a referral hospital type B in Maduraisland, but there has never been a Plastic Surgery specialist services before 2015. This research isdone to know the epidemiology of Plastic surgery cases treated at Syarifah Ambami Rato EbhuHospital Madura in two years. The study was a descriptive retrospective observational study with asample of the entire population of outpatient and inpatient handled by Plastic Surgeon in a span oftwo years. The case of Plastic Surgery Data collected show an increase in patients as much as 34.1%of 129 patients in 2015 to 173 patients in 2016, the case has risen significantly by 130% from 23cases in 2015 to 53 cases in the year 2016, and the non-operative cases increase by 13.2% from 106cases to 120 cases with details of the five most cases are handled by a specialist plastic surgery are:chronic wounds with a total of 72 cases has increased 127% in year 2, wounds fuels with a total of35 cases has increased 18.75% in year 2, vulnus appertum as many as 31 cases increased by38.46% in the year-to-two years, as many as 25 cases of keloid has increased 50% in year 2 years,and basalioma with a total of 23 cases, decreased 35.7% in year 2 years after the holding extension.The case of Plastic Surgery and the number of patients has increased significantly since the holdingof Plastic Surgery services in Syarifah Ambami Rato Ebhu Bangkalan hospital. Unfortunately thisservice is discontinued. Therefore, it should be a Plastic Surgeon specialist service continuously inBangkalan hospital Madura, supporting Presidential Decree No.04 in 2017 to assist the efficiencyand effectiveness of the Maduranese who require specialist services in plastic surgery.